Achieving healthy brand status: a case study on Natal Action Netball Association - Da Silva, Nikita (The IIE, 2016)
Vega School of Brand Leadership cofounder Gordon Cook and some fellow writers created an article that asks organisations ‘How Healthy is Your Brand?,’ this article gives organisations seven criteria to put their brand through, a brand audit. In this paper four of the criteria is looked at in-depth with it being adapted to fit a small non-profit sports organisation. This brand is Natal Action Netball Association (which will be referred to as NANA from here on) a small organisation that is run as a hobby only in Kwa-Zulu Natal (which will be referred to as KZN from here on) to create KZN action netball. Through secondary research such as case studies and primary research such as focus groups and participant observation the following statement can be made. As a brand NANA does not have what is synonymous with what is necessary to say it is branded. They follow no systems that are stated in the branding environment leaving their organisation unrecognisable (brand identity), lack in dialogue between the brand and its stakeholders (brand communication), no understanding of their reason of existence to players (brand value) and no understanding to what they do for players (brand purpose). This paper looks at these four criteria in depth and the various frameworks that can be used by NANA to guide them to a healthy brand.
Theses
Keywords: Natal Action Netball Association; Healthy branding status; Brand identity; Brand value; Brand purpose